Residue analysis and risk assessment of tebuconazole in jujube (Ziziphus jujuba Mill). (5th February 2017) - You, Xiangwei; Li, Yiqiang; Wang, Xiuguo; Xu, Jinli; Zheng, Xiao; Sui, Chengcheng
Abstract: In this study, a sensitive and reliable analytical method, based on a modified Quick, Easy, Cheap, Effective, Rugged and Safe procedure, was established for determination of tebuconazole in jujube. After extraction with acetonitrile, the samples were cleaned up by dispersive solid‐phase extraction with primary secondary amine, and determined by high‐performance liquid chromatography tandem mass spectrometry. At fortification levels of 0.01, 0.1 and 2.0 mg kg −1, the average recoveries of tebuconazole in jujube were in the range 97.6–101.9%, with relative standard deviations of 1.5–3.5%. The dissipation and residual levels of tebuconazole in jujube under field conditions were investigated. Tebuconazole dissipated relatively slowly in jujube, with a half‐life of 33.0 days. The terminal residue experiments of tebuconazole in jujube were conducted in four locations in China and the risk was evaluated using risk quotients ( RQ ). RQ values were found to be significantly lower than RQ = 1, indicating that the risk to human health of using the recommended doses of tebuconazole in jujube was not significant. This study could provide guidance for the safe and reasonable use of tebuconazole in jujube and serve as a reference for the establishment of limit of maximum residue in China.